Economic Regions Based on the Agglomeration Economics: an Evaluation for the Spanish Case. - Fernando Rubiera Morollon; Ana Vi\~nuela (European Regional Science Association (ERSA), 2011)
What is region? From an economic point of view, a region is a unit in which capital and labour move freely and goods and services are totally open to trade with other regions without any frontiers or limitations. The openness of the regions and their interaction with other regions are their main characteristics. From a statistical point of view internal homogeneity and also heterogeneity between the regions are both desirable properties of a set of regions. The objective of this chapter is revise the concept of region and propose a division of the territory which satisfy the statistical and economical region concept requirements in the way of propose a classification that has economic theoretical meaning but, at the same time, satisfy the internal homogeneity and heterogeneity among classes. Using micro data from the latest Census available, the Spanish territory can be divided into functional regions that emphasize the importance of location and agglomeration economies (a classification with theoretical economic meaning). A set of contrast and indexes is applied to prove that, when studying labor economic issues, such classification based on economic criteria results on more convenient regions than the administrative ones commonly used.
Keywords: 330